PERBANDINGAN PENDEKATAN TEORITIS INTERNATIONAL ACCOUNTING STANDARD (IAS) 41 DAN PSAK 16 PADA BIAYA TANAMAN BELUM MENGHASILKAN KARET (STUDI KASUS DI PT. PERKEBUNAN MITRA OGAN (RNI GROUP) DI PALEMBANG) - Desak Nyoman Lestari; Burhanuddin Burhanuddin; Abu Kosim (AKUNTABILITAS, 2017)
This Reseachis aimed to determinethe calculation of immature plant cost based on International Accounting Standard (IAS) 41 and PSAK 16 in PT. Perkebunan Mitra Ogan (RNI GROUP) in Palembang. This research uses descriptive method with the data obtained is primary and secondary data. The biological asset consist if two immature plants (TBM) and yielding plant (TM). Immature plants is plant that has not yielded results, still young, has never flowered or not enought age to produce, while the plant produces a plant that is ready to be harvested. Cost of immature palntation costs such as land preparation, maintenance, fertilization, grras cutting and maintenance costs. The cost of the plant has not, the yield will be reclassified into the yield crop (TM) it aims to add value from the biological asset it self. In a company the measurement of biological assets based on cost (historical value), while in International Accounting Standard (IAS) 41 using fair value. The results show that fair value of the plant has not been produced by International Accounting Standard (IAS) 41 is smaller than the value the cost of immature crops according to PSAK 16 it is quoted in PT. Perkebunan Mitra Ogan (RNI GROUP) no aktive market for biological assets.